Pleiotropic Effects of Simvastatin and Losartan in Preclinical Models of Post-Traumatic Elbow Contracture - David, Michael A.; Reiter, Alex J.; Dunham, Chelsey L.; Castile, Ryan M.; Abraham, James A.; Iannucci, Leanne E.; Shah, Ishani D.; Havlioglu, Necat; Chamberlain, Aaron M.; Lake, Spencer P. (Frontiers in Bioengineering and Biotechnology, 2022)
Elbow trauma can lead to post-traumatic joint contracture (PTJC), which is characterized by loss of motion associated with capsule/ligament fibrosis and cartilage damage. Unfortunately, current therapies are often unsuccessful or cause complications. This study aimed to determine the effects of prophylactically administered simvastatin (SV) and losartan (LS) in two preclinical models of elbow PTJC: an in vivo elbow-specific rat injury model and an in vitro collagen gel contraction assay. The in vivo elbow rat (n = 3–10/group) injury model evaluated the effects of orally administered SV and LS at two dosing strategies [i.e., low dose/high frequency/short duration (D1) vs. high dose/low frequency/long duration (D2)] on post-mortem elbow range of motion (via biomechanical testing) as well as capsule fibrosis and cartilage damage (via histopathology). The in vitro gel contraction assay coupled with live/dead staining (n = 3–19/group) evaluated the effects of SV and LS at various concentrations (i.e., 1, 10, 100 µM) and durations (i.e., continuous, short, or delayed) on the contractibility and viability of fibroblasts/myofibroblasts [i.e., NIH3T3 fibroblasts with endogenous transforming growth factor-beta 1 (TGFβ1)]. In vivo, no drug strategy prevented elbow contracture biomechanically. Histologically, only SV-D2 modestly reduced capsule fibrosis but maintained elevated cellularity and tissue hypertrophy, and both SV strategies lessened cartilage damage. SV modest benefits were localized to the anterior region, not the posterior, of the joint. Neither LS strategy had meaningful benefits in capsule nor cartilage. In vitro, irrespective of the presence of TGFβ1, SV (≥10 μM) prevented gel contraction partly by decreasing cell viability (100 μM). In contrast, LS did not prevent gel contraction or affect cell viability. This study demonstrates that SV, but not LS, might be suitable prophylactic drug therapy in two preclinical models of elbow PTJC. Results provide initial insight to guide future preclinical studies aimed at preventing or mitigating elbow PTJC.